2012
DOI: 10.4314/ijbcs.v5i5.13
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalysis of <em>H. sabdariffa</em> during ‘dawadawan botso’ production and biogeneration of volatile compounds

Abstract: The analysis of free amino acid and volatile compounds were conducted to understand how the fermenting organism's biocatalyse H. sabdariffa seeds and its role in the biogeneration of free amino acids and flavour compounds in "dawadawan botso". Fermentation increased the quantity of all essential amino acids except of threonine which decrease by 1.23 g/100 g protein. Arginine had the highest increase with a value of 3.06 g/100 g protein while proline had the least value of 0.22 g/100 g protein. Fermentation inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The volatile compound identified in dawadawa was more the number previously reported by [3]. The difference could be attributed to either the solvent used for extraction of the volatile compound or the column used for the gas chromatography.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The volatile compound identified in dawadawa was more the number previously reported by [3]. The difference could be attributed to either the solvent used for extraction of the volatile compound or the column used for the gas chromatography.…”
Section: Discussionmentioning
confidence: 59%
“…Fermentation was found to increase the quantity of all essential amino acids except of threonine and an increase in the total free amino acid was also observed following fermentation of the H. sabdariffa seeds. The profile of bitter, sweet and MSG-like free amino acids in the unfermented and fermented seeds were also different [3]. In the same study, 22 volatile compounds were identified from the fresh "dawadawan botso" and locally produced dried "dawadawan botso" and the compounds include alcohols, acids, aldehydes, esters, and alkanes.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The products of lipid and protein degradation play a vital role on the nutritional status of these condiments while also directly contributing to the taste characteristics and in some cases, indirectly serve as aromatic products precursors (Kiers et al, 2000;Han et al, 2004). It is well documented in the literature that the majority of taste compounds such as salt and amino acids produced during proteolysis are contained in the water-soluble fraction (Kim and Lee, 2003), and the quality indices of many legume based fermented condiments such as free amino acids have been reported (Omafuvbe et al, 2000;Kim and Lee, 2003;Han et al, 2004, Ouoba et al, 2005, Ibrahim et al, 2011Ojinnaka and Ojimelukwe, 2013).…”
Section: Introductionmentioning
confidence: 99%